2017
DOI: 10.1002/2017ja024227
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence in Three‐Dimensional Simulations of Magnetopause Reconnection

Abstract: We present detailed analysis of the turbulence observed in three‐dimensional particle‐in‐cell simulations of magnetic reconnection at the magnetopause. The parameters are representative of an electron diffusion region encounter of the Magnetospheric Multiscale (MMS) mission. The turbulence is found to develop around both the magnetic X line and separatrices, is electromagnetic in nature, is characterized by a wave vector k given by kρe∼(meTe/miTi)0.25 with ρe the electron Larmor radius, and appears to have the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
77
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 41 publications
(95 citation statements)
references
References 26 publications
17
77
0
Order By: Relevance
“…The conclusion is that the magnetopause models do not very well represent the observed current sheet orientation. This is evidence for a large local deformation of the magnetopause, such as could result from a “lower‐hybrid drift‐like instability” (Ergun et al, ; Le et al, ; Price et al, ), the Kelvin‐Helmholtz instability or a plasma/field structure from the solar wind impinging on the magnetopause.…”
Section: Magnetopause Models: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conclusion is that the magnetopause models do not very well represent the observed current sheet orientation. This is evidence for a large local deformation of the magnetopause, such as could result from a “lower‐hybrid drift‐like instability” (Ergun et al, ; Le et al, ; Price et al, ), the Kelvin‐Helmholtz instability or a plasma/field structure from the solar wind impinging on the magnetopause.…”
Section: Magnetopause Models: Resultsmentioning
confidence: 99%
“…We conclude that there must have been a large, spatially and temporally localized, deformation of the magnetopause shape during the event, causing a large deviation of the predicted normal direction from the Shue and Lin models. The physical reason for this behavior remains unclear but is possibly related to localized reconnection activity in combination with a lower‐hybrid drift‐like instability (Ergun et al, ; Le et al, ; Price et al, ), large‐amplitude Kelvin‐Helmholtz waves, or a plasma/field structure from the solar wind impinging on the magnetopause.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the long duration of the magnetopause crossing (∼30 s), it is possible that the configuration of the magnetopause changed over the course of the event. It is also possible that kinetic‐scale instabilities cause the local current and boundary orientations to differ from the larger‐scale configuration (Ergun, Holmes, et al, ; Ergun et al, ; Price et al, , ). Four‐point timing analysis (Schwartz, ) of the B Z G S E reversal point (at approximately 07:36:55 UT) yields a normal vector of [0.98011, 0.192104, −0.049797], again in GSE, and a boundary velocity of −31 km/s trueN̂.…”
Section: Data Analysis Methods and Lmn Coordinatesmentioning
confidence: 99%
“…This structured magnetopause was similar in character to the corrugated magnetopause of Ergun et al () and the lower hybrid drift turbulence of Roytershteyn et al (). Price et al, noted that the wrapping of the normal electric field E N into the direction of the current ( M ) resulted in greatly enhanced trueJ·trueE. Le et al (), which analyzed a 3‐d simulation of the same event studied by Price et al (, ), found that these oscillations in the current layer caused intense parallel electron heating as was observed by MMS (Burch et al, ).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation